Abstracts as a Basis for Relevance Judgment - Hagerty, Katherine; Chicago Univ., IL. Graduate Library School ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1967)
The purpose of the study was to determine how many questions judged relevant to an article are also judged relevant using different length representations of the article, and how this proportion changes as the length of the representation changes. Several persons made relevance judgments for each of a set of articles to each of a set of questions. For each article several different length representations, titles and abstracts, were used as the basis for relevance judgments. The study showed that the title alone was quite effective in making relevance judgments and that even with a 300 word abstract, this effectiveness in terms of recall and precision, was not doubled. However, the use of an abstract did increase the recall and precision, but the results of the study do not suggest an optimal abstract length. (Author/NH)
Sponsoring Agency: National Science Foundation, Washington, DC.
ERIC Note: (39 References); Studies in Indexing Depth and Retrieval Effectiveness.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Abstracts; Experimental Programs; Indexing; Information Processing; Information Retrieval; Information Seeking; Information Systems; Relevance (Information Retrieval)